DIFFERENCES IN BODY COMPOSITION BETWEEN SOCCER PLAYERS AND NON- ATHLETES - Željko Zombra, (Sport Scientific And Practical Aspects, 2025)
he aim of this study was to determine the differences in body composition between seccer players and non-athletes. The research was conducted over 48 respondents, 26 soccer athletes (aged 18 to 32) and 22 non-athletes (18 to 38 years old). The assessment of the body composition was based on the BIA technology on tanita scale (the model BC545N, and the variables taken into consideration in this measure are years of life, height, weight, BMI, percentage of body fat, percentage of water and percentage of free fat mass. Height was measured with anthropometer by Martin. The results of the analysis were made in the SPSS program package. For all the data collected in this study, descriptive statistics are presented, the central and dispersive parameters are calculated, and the distribution of normality is determined, while the differences in the variables for assessing the body composition are determined by T test for independent samples. The results showed that a statistically significant difference exists in 6 variables: AGE (t = -3.036 with coefficient of significance p = 0.04, which is far below the theoretical limit of 0.05. Variable weight in kilograms: TTKG (t = -3.685, with coefficient of significance p = 001), BMI variable (t = -3.180, coefficient of significance p = 004), body fat BFAT% ( t = -5,579, with the significance coefficient p =, 000), then the variable VODA% (t = 6,285, p =,000), and the variable percentage value of the muscle mass MISMASS% (t = 5,675 with the coefficient of significance p = .000).